A single-letter change in an acronym: signals, reasons, promises, challenges, and steps ahead for moving from NAFLD to MAFLD - YILMAZ, YUSUF (TAYLOR & FRANCIS LTD, 2021)
Introduction: We are currently at the dawn of a revolution in the field of fatty liver diseases. Recently, a consensus recommended 'metabolic (dysfunction) associated fatty liver disease' (MAFLD) as a more appropriate name to describe fatty liver disease associated with metabolic dysfunction, ultimately suggesting that the old acronym nonalcoholic fatty liver disease (NAFLD) should be abandoned. Areas covered: In this viewpoint, we discuss the reasons and relevance of this semantic modification through five different conceptual domains, i.e., 1) signals, 2) reasons, 2) promises, 4) challenges and 5) steps ahead. Expert opinion: The road ahead will not be traveled without major challenges. Further research to evaluate the positive and negative impacts of the nomenclature change is warranted. However, this modification should encourage increased disease awareness among policymakers and stimulate public and private investments leading to more effective therapy development.
Keywords: Disease rebranding; metabolic (dysfunction) associated fatty liver disease; nomenclature; nonalcoholic fatty liver disease